Alleles of apolipoprotein E gene (APOE) as genetic determinants of dementia - Akter, Seikh Farid Uddin; Abdul Rani, Mohammed Fauzi; Ab Rahman, Jamalludin; Sulong, Sarina; Md Aris, Mohd Aznan; Phang, Ing Chia; Khattak, Muhammad Muzaffar Ali Khan; Bakhtiar, M. Taher (2012)
Dementia is emerging as a silent epidemic for rapidly developing countries like Malaysia. Its prevalence and a generic determinant assessment were the focused objectives of this study. There were two phases in this study - an initial descriptive phase followed by an analytic phase. Data were collected from 197 study subjects intially for the secriptive phase; 65 dementia cases and 103 age matched controls for analytic phase using a questionnaire for personal profile and other related factors. Furthermore, the standard protocols were followed to determine the frequencies of the alleles of apolipoprotein E gene (APOE). The statistical analyses were performed using the SPSS for Windows, Version 17. In addition to descriotive statistics such as percentage, pertinent inferential statistical analyses such as chi square test were performed. It appears from the inital descriptvie study that dementia was the leadinf disease (72.1%) of the identified diseases among study subjects.